FAKTOR – FAKTOR YANG MEMPENGARUHI KEJADIAN DIARE PADA MASYARAKAT DI DESA PATUMBAK 1 DUSUN VII - Yunita Syahputri Damanik; Sri Sudewi Pratiwi Sitio; Nada Amirah; Muhammad Rifqi Azhary; Efrata S (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2023)
Diarrhea is still a public health problem in developing countries such as Indonesia, because of its high morbidity and mortality. Most diarrhea occurs in children under the age of 2 years. Toddlers aged 12-24 months have a risk of diarrhea 2.23 times compared to children aged 25-59 months. The purpose of this research was to see the influence of knowledge, attitudes, behavioral factors, environmental factors with the incidence of diarrhea in the hamlet VII Patumbak 1. The research method used descriptive observational with a cross sectional approach. The sample was carried out by purposive sampling. The instrument in this research was using a questionnaire. Analysis of this data using Chi Square statistical test. The results showed that there was an influence between knowledge and the incidence of diarrhea (P value 0.005). There was an influence between attitude and the incidence of diarrhea with a P value 0.002 (<0.05). There was an influence between behavioral factors and the incidence of diarrhea with a P value 0.003 (<0.05). There was an influence between environmental factors and the incidence of diarrhea with a P value 0.001 (<0.05). It is necessary to inform the local government to always monitor and socialize to the public about the factors that influence diarrhea.